Answer:
6 pounds.
Step-by-step explanation:
70-25.36= 44.64 (the amount of money she spent)
44.64/7.44 (per pound cost)= 6
Answer:
Rachel bought 6 pounds of coffee.
Step-by-step explanation:
First, do $70-$25.36, because that will give you the total amount of money she spent on coffee.
$70-$25.36= $44.64.
Rachel spent $44.64 on coffee.
Next, you know that every pound of coffee costs $7.44.
So, $7.44x = $44.64
x= the number of pounds of coffee Rachel purchased.
So, we have to now isolate x.
$7.44x / $7.44 = $44.64 / $7.44
x= 6
Therefore, Rachel purchased 6 pounds of coffee.
If you need anymore help on any math problems, email me at: [email protected]
I also tutor.
Hope this helps:)
A swimming pool measures 35 feet wide by 50 feet long. What is the ratio of the length to the perimeter
The ratio of length to perimeter of pool is 5 : 17
Given that, swimming pool measures 35 feet wide by 50 feet long
Therefore,
Length = 50 feet
Width = 35 feet
Swimming pool is usually of rectangular shape
The perimeter of rectangle is given as:
Perimeter = 2(length + width)
Perimeter = 2(50 + 35)
Perimeter = 2(85) = 170
Thus perimeter of pool is 170 feet
Ratio of length to perimeter:
Thus ratio of length to perimeter of pool is 5 : 17
Answer:
15
Step-by-step explanation:
Square root of 5=√5
Square of the square root=(√5)^2
=5
Square root of 3=√3
Square of the square root=(√3)^2
=3
So (square root of 5)^2×(square root of 3)^2
5×3
15
Therefore the final answer is 15
Answer:
16 yards
Step-by-step explanation:
The altitude (red line) and the other side multiply to 16.
Answer:
16 yd
Step-by-step explanation:
If two lines intersect, then there are two possibilities
A) The lines intersect at exactly one point. This happens if the slopes of the two lines are different (the y intercepts may or may not be the same).
B) The lines intersect at infinitely many points. This happens when both slopes are the same and when both y intercepts are the same. In short, the two equations are identical. Often they may be written in different forms. For example, the equation y = 2x+1 and 2y = 4x+2 are the same equation. Divide everything in equation (2) by 2 and you'll get equation (1).